2021
DOI: 10.21203/rs.3.rs-787983/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sulforaphane prevents and reverses allergic airways disease in mice via anti-inflammatory, antioxidant and epigenetic mechanisms

Abstract: Sulforaphane has been investigated in human pathologies and preclinical models of airway diseases. To provide further mechanistic insights, we explored L-sulforaphane (LSF) in the ovalbumin (OVA)-induced chronic allergic airways murine model, with key hallmarks of asthma. Histological analysis indicated that LSF prevented or reversed OVA-induced epithelial thickening, collagen deposition, goblet cell metaplasia, and inflammation. Well-known antioxidant and anti-inflammatory mechanisms contribute to the benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
1
0
1
Order By: Relevance
“…To further understand these changes, gene expression data in the present study was compared to published RNAseq data from in vitro sulforaphane-treated human PBMC (27). In the additional dataset analysed, several of the B-cell associated genes upregulated in the present dataset showed the opposite trend in PBMCs, in support of results from murine models.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…To further understand these changes, gene expression data in the present study was compared to published RNAseq data from in vitro sulforaphane-treated human PBMC (27). In the additional dataset analysed, several of the B-cell associated genes upregulated in the present dataset showed the opposite trend in PBMCs, in support of results from murine models.…”
Section: Discussionsupporting
confidence: 65%
“…Downregulated pathways include inflammatory cytokine production and also response to oxidative stress, demonstrating significant anti-inflammatory effects. Notably, however, several Nrf2associated genes unaltered by SFX-01 in our study, including NQO1, GPX, HMOX1, GSS and G6PD, also showed no significant differences with L-SFN treatment in human PBMCs at this timepoint (27).…”
Section: Differences In Effects Of Sfx-01 Treatment In Vivo and L-sfn...contrasting
confidence: 73%